Using personas and the ADKAR framework to evaluate a network designed to facilitate sustained change toward active learning in the undergraduate classroom - Amy J. Prunuske; Heather J. Evans-Anderson; Katherine L. Furniss; Carlos C. Goller; Jaime E. Mirowsky; Michael E. Moore; Samiksha A. Raut; Uma Swamy; Sue Wick; Michael J. Wolyniak (Springer, 2022)
Abstract One promising practice for increasing active learning in undergraduate science education is the use of a mentoring network. The Promoting Active Learning and Mentoring (PALM) Network was launched with practitioners from several professional societies and disciplines to make changes in their teaching based on evidence-based practices and to encourage the members to reflect deeply on their teaching experiences. Members of the Network interviewed seven previous Fellows, 1 to 6 years after completing their fellowship, to better understand the value of the Network and how these interactions impacted their ability to sustain change toward more active teaching practices. The interviews resulted in the creation of three personas that reflect the kinds of educators who engaged with the Network: Neil the Novice, Issa the Isolated, and Etta the Expert. Key themes emerged from the interviews about how interactions with the PALM Network sustained change toward evidence-based teaching practices allowing the members to readily adapt to the online learning environment during the COVID-19 pandemic. Understanding how the personas intersect with the ADKAR model contributes to a better understanding of how mentoring networks facilitate transformative change toward active learning and can inform additional professional development programs.